The Effectiveness of Play Therapy and Positive Reinforcement to Reduce Gadgets Addiction in Children - Gusti Ayu Nyoman Triana Dewi (Proceedings of The ICECRS, 2020)
Addiction to gadgets refers to the loss of control, obsessive behavior, interpersonal problems, lack of tolerance, signs of antisocial which lead to dependency on gadgets. The intervention in this research was administered is to reduce the addiction to gadgets by promoting children to play without using gadgets. This research was conducted in a single-subject design with three phases, namely the base line phasein which several behaviors were determined to be intervened, intervention phase and finally the baseline evaluation phase. Research data were collected through interviews (autoanamnesa and alloanamnesa), observation and psychological tests including Forer, CAT, and HTP. The subject of this research was a 5-year-old girls who suffered from gadget addiction. The intervention was carried out in three stages for 20 days, each of which lasted for 2 hours. In the first stage, rapport and therapeutic contracts were administered and play therapy without using gadgets was done, and rewards were given when the subject successfully did the task. The last stage was the termination of all activities that had been carried out. The interventions carried out in this research showed significant behavioral changes. Before the intervention, the subject spent 6-7 hours per day to play gadgets. The subject always cried when going to school and was less interested in playing games with his friends. After the intervention, the subject started to do her daily activities with lesser screen time and longer time to play with friends without gadgets. The subject also started to get ready for school every morning.